Ligustrazine inhibits inflammatory response of human endometrial stromal cells through the STAT3/IGF2BP1/RELA axis - Ying Feng; Han Dong; Liyan Zheng (Taylor & Francis Group, 2023)
AbstractContext Endometriosis (EMs) is a gynecological disorder. Ligustrazine has been reported to exert an anti-inflammatory effect on EMs. However, the underlying mechanisms are not completely understood.Objective To investigate the effects of ligustrazine on the progression of EMs and the underlying regulatory mechanisms.Materials and methods Human endometrial stromal cells (HESCs) were isolated from patients with EMs or control subjects. HESCs were treated with 25, 50, 100, or 200 μM ligustrazine for 1, 3, 6, or 12 h. Western blot and enzyme-linked immunosorbent assays were performed to determine the levels of proteins and inflammatory cytokines, respectively. The binding between STAT3 and insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) was assessed by chromatin immunoprecipitation and dual-luciferase reporter assays. The relationship between IGF2BP1 and RELA was assessed by RNA immunoprecipitation and RNA pull-down assay.Results Phosphorylated STAT3, IGF2BP1, RELA, TNF-α, IL-6, and IL-1β were upregulated in EMs tissues compared with control tissues (by 1.79-, 2.55-, 1.58-, 3.01-, 2.55-, and 3.34-fold, respectively). Ligustrazine inhibited the expression of p-STAT3, IGF2BP1, RELA, IL-6, TNF-α, and IL-1β. Overexpression of STAT3 promoted RELA-mediated inflammatory responses, while ligustrazine (100 µM) notably reversed this phenomenon. Ligustrazine also alleviated RELA-induced inflammation via downregulating IGF2BP1. STAT3 bound to the promoter of IGF2BP1, and IGF2BP1 bound to the RELA mRNA.Discussion and conclusion Ligustrazine inhibited inflammation in EMs via regulating the STAT3/IGF2BP1/RELA axis. These findings propose a new agent against EMs and support the development of ligustrazine-based treatment strategies for EMs.